Pengaruh Media Pembelajaran Flip Book Terhadap Motivasi, Kemandirian, dan Hasil Belajar Biologi Peserta Didik SMA Pulau Barrang Lompo Makassar - Abdul Gafur (UNM Journal of Biological Education, 2021)
AbstractThis research is a quasi experimental posttest only control group design and pretest–posttest non equivalent control group design which aims to determine the differences in motivation, independence, and learning outcomes of students. The sample of this study was selected in survei and selected class XI MIPA 1 as the experimental class and XI MIPA 2 as the control class. Data collection techniques through the provision of questionnaires to measure motivation and learning independence and the provision of multiple choice tests to measure biology learning outcomes. The data analysis technique used is descriptive and inferential statistical analysis with t-test. The results showed that (1) learning motivation through flip book learning media and textbook learning media for Barrang Lompo Island High School Makassar students were on average in the high category and the medium category. (2) Learning independence through flip book learning media and textbook learning media for Barrang Lompo Island High School Makassar students are on average in the high category and the medium category. (3) Learning outcomes through flip book learning media and textbook learning media for students at Barrang Lompo Island High School Makassar are on average in the high category and the medium category. (4) There are differences in learning motivation through flip book learning media and textbook learning media for students at Barrang Lompo Island High School Makassar. (5) There are differences in learning independence through flip book learning media and textbook learning media for students at Barrang Lompo Island High School Makassar. (6) There are differences in learning outcomes through flip book learning media and textbook learning media for students at Barrang Lompo Island High School Makassar.